Hydrodynamic evolution near QCD critical point - Aguiar,C. E. (2007)
Some consequences of the presence of critical point in the equation of state on the hydrodynamical evolution of the strongly interacting matter are discussed. For this purpose, we apply the low energy effective theory of QCD, the Nambu-Jona-Lasinio model and show some examples.